The Influence of Work Culture and Work Ability on Organizational Commitment in The Directorate of Special Criminal Research of The Metro Jaya Regional Police (Dinasti International Journal of Management Science, 2026)
The purpose of this study is to describe and analyze the influence of work culture on organizational commitment, the influence of work ability on organizational commitment and to analyze the influence of work culture and work ability on organizational commitment at the Directorate of Special Criminal Investigation of the Metro Jaya Regional Police. The calculated tvalue for the Work Culture variable (X1) is 4,726, while the ttable value for N = 64 is 1,997. So 4,726 > 1,997, then H0 is rejected and Ha is accepted, Work Culture (X1) has a significant effect on Organizational Commitment (Y). The calculated tvalue for the Work Ability variable (X2) is 8,899, while the ttable value for N = 64 is 1,997. So 8,899 > 1,997, then H0 is rejected and Ha is accepted. The calculated Fvalue is 105,076 Meanwhile, the Ftable ( a0,05) for N = 64 is 2,75. So the calculated F is > from the Ftable (a0,05) or 105,076 > 2,75 with a significance level of 0,00 0 because 0,000 < 0,05, it can be said that Work Culture (X1) and Work Ability (X2) together or simultaneously have a positive effect on Organizational Commitment (Y), the R Square value (R2) is 0,775. This shows that 77,5% Work Culture (X1) and Work Ability (X2) jointly influence Organizational Commitment (Y), while the remainder is 22,5% influenced by other factors not examined in this study.